Penggunaan Media Pembelajaran Sparkol Vidioscribe Untuk Meningkatkan Hasil Belajar Siswa Kelas XI TKJ 1 Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Materi Perawatan Jenazah Di SMK Negeri 1 Nganjuk - Romdoni, Mohamad; Rasyid, Fathor; Saifullah, Saifullah (Allimna: Jurnal Pendidikan Profesi Guru, 2022)
Every time they teach, teachers need to make teaching preparations in order to carry out part of the monthly plan and yearly plan. In the preparation it has been contained about, the purpose of teaching, the subject to be taught, teaching methods, lesson materials, teaching aids and evaluation techniques used. Based on the results of initial observations made in class XI TKJ 1 SMKN 1 Nganjuk, it was revealed that there were still many students who did not pay attention to the teacher's explanation when the process of explaining the subject matter. Students tend to be passive when the learning process takes place, students are sleepy and bored when the teacher explains material about corpse care, and the results of the mid-semester assessment are still many who have not reached the expected minimum completeness criteria (KKM) which is 70 and above, 45% of students whose test results are still below the criteria minimum completeness (KKM) before remedial. The problems to be studied in this classroom action research are: (a) How is the application of the Sparkol Vidioscribe learning media in improving the learning outcomes of class XI students of SMKN 1 Nganjuk in PAI learning with material on procedures for organizing corpses? (b) Can the application of the Sparkol Vidioscribe learning media improve the learning outcomes of class XI students of SMKN 1 Nganjuk in PAI learning with material on procedures for organizing corpses?. The research objectives to be obtained are: (a) To find out the application of the Sparkol Vidioscribe learning media in improving student learning outcomes in Islamic Religious Education (PAI) subjects. (b) To find out how much the use of Sparkol Vidioscribe learning media can improve student learning outcomes in Islamic Religious Education (PAI) subjects. This study uses two cycles of action research. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study was the students of class XI. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student achievement increased from pre-cycle to cycle II, namely, pre-cycle (56%), cycle I (72%), cycle II (83%). The conclusion of this research is the application of sparkol vidio scribe learning media can improve student achievement in class XI TKJ 1, and this learning model can be used as an alternative to effective and efficient Islamic Religious Education learning.